A touching case of channel regulation: the ATP-sensitive K+ channel. - Tucker, S; Ashcroft, F (1998)
The classical type of KATP channel is an octameric (4:4) complex of two structurally unrelated subunits, Kir6.2 and SUR. The former serves as an ATP-inhibitable pore, while SUR is a regulatory subunit endowing sensitivity to sulphonylurea and K+ channel opener drugs, and the potentiatory action of MgADP. Both subunits are required to form a functional channel.